'Shaking Hands with Money': The Phenomenon of Gap in Modern Uzbekistan and Kazakhstan. Issue 6 (3rd July 2017) - Alexandrov, Timur
Abstract: This study examines gap— traditional reciprocal associations common in Central Asia. Gap is an unofficial, regular get-together of people of similar age bound by socially acknowledged ties. The study argues that gap represents a communal type of civil society featuring many differences from analogous groups in Western liberal societies. Gap may effect social consciousness and facilitate mobilisation. The study also analyses modern forms of gap such as joint savings funds, female-only get-togethers, and internet-based gap .